2020
DOI: 10.2147/rmhp.s280289
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Impact and Associated Factors of COVID-19 on the General Public in Hunan, China

Abstract: This study aimed to assess the psychological impact of the COVID-19 pandemic among the general public in Hunan Province, China, which could help develop psychological interventions and mental health programs. Participants and Methods: This online cross-sectional study recruited 571 participants through snowball sampling between February 2 and February 5, 2020. Data were collected through a general information questionnaire, the Public Emergency Psychological State Questionnaire, the Simple Coping Style Questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“…As found in the study, 43% of the participants (translating into 172 in 400 older adults) have somewhat suffered psychological distress from COVID-19. This finding showed a higher incidence of psychological distress among the respondents compared to the findings from earlier studies on psychological distress due to COVID-19 [21,[23][24][25][26]. The moderate level of stress reported in our study lends credence to the similar finding discovered by Grover et al (2020).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As found in the study, 43% of the participants (translating into 172 in 400 older adults) have somewhat suffered psychological distress from COVID-19. This finding showed a higher incidence of psychological distress among the respondents compared to the findings from earlier studies on psychological distress due to COVID-19 [21,[23][24][25][26]. The moderate level of stress reported in our study lends credence to the similar finding discovered by Grover et al (2020).…”
Section: Discussionsupporting
confidence: 87%
“…Nania et al [2] also posited that adolescents' quest to understand the reasons behind social stratifications in their societies induce the feeling of anxiety and worry in them especially when they belong to the disadvantaged end of the spectrum. Psychological distresses are more prevalent among the young adult category (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and the older adult group (above 60 years) [3]. Vahedian-Azimi and others further explained that access to diversified information on social media incubates anxiety and some sense of worry among young adults whereas depression, which is induced by loneliness and regret, is common among people within the older age group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,18 It was also noted that such an avoidant coping style affected individuals' psychological distress more than an active coping style during the lockdown period. 18,19 A study revealed that a positive attitude and trust in God were the most used adaptive coping strategies during the pandemic. 20 Further, given the collectivistic essence of Indian society, it was observed that seeking social support was the highest used coping strategy in India.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has shown long-term biological consequences of stress [29,47]. Therefore, how one copes is significantly related to how these psychological stressors are handled in the COVID-19 pandemic and ultimately influences health outcomes [50].…”
Section: Introductionmentioning
confidence: 99%